Marketing Approaches for Increasing the Competitiveness of Air Transport - Tzvetkova, Svetla (Research Papers, 2018)
The marketing criteria of consumers in air transport have increased significantly in recent years – consumers have become more informed and harder to please. In order to properly respond to this challenge, air companies have focused their efforts on developing direct sales, created programs for encouraging frequently travelling passengers, formed alliances and used a multitude of other measures towards expanding market shares, reducing expenses, etc. At the same time, the dynamic and competition on the global air market have necessitated the development and implementation of new approaches in solving the goals that air companies face in terms of marketing. The topicality of the problem is the basis for the motivation behind the choice of topic for this paper, whose purpose is to analyze marketing approaches for increasing the competitiveness of air companies according to the example of the UAE’s national carrier – Etihad Airways. On the basis of an analysis of scientific literature in the field of marketing, as well as statistic and accounting documents related to the air company’s activity, it has been concluded that Internet relations, globalization, the dynamic of the transport market and the unprecedented changes in economy have forced air companies to reconsider their market strategies and marketing approaches in order to improve their competitiveness.